2017
DOI: 10.3126/jkmc.v4i3.18238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mid-trimester abortion: A way forward

Abstract: Abstract:Background: Need of second trimester abortion has been increasing because of the wide scale introduction of prenatal screening programs detecting women whose pregnancies are complicated by serious fetal abnormalities. Lack of accredited centers and skills required for mid trimester abortion have made this procedure inaccessible to rural population of Nepal. Objectives: This study was conducted to assess correlation of uterine size measured by clinical examination and that assessed by ultrasound, foeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The first onset of menstruation usually occurs in girls between the ages of 11 and 14 years and is often considered an indicator of puberty and sexual maturity. Previous studies have indicated that menstruation is subjected to several forms of stigma and is also considered a source of pollution and impurity, in some communities [2][3][4][5]. Girls in some countries follow myths, taboos, and socio-cultural restrictions in relation to clothing, food, and physical activities during menstruation, and even fear revealing about it [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first onset of menstruation usually occurs in girls between the ages of 11 and 14 years and is often considered an indicator of puberty and sexual maturity. Previous studies have indicated that menstruation is subjected to several forms of stigma and is also considered a source of pollution and impurity, in some communities [2][3][4][5]. Girls in some countries follow myths, taboos, and socio-cultural restrictions in relation to clothing, food, and physical activities during menstruation, and even fear revealing about it [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these practices may be helpful, but others have potentially harmful implications [6]. In addition to these, symptoms like menstrual cramps, mood changes, and feeling sick (which can occur normally during menstruation), significantly contribute to women having unpleasant feelings and attitudes towards menstruation [4,7]. These menstrual beliefs and practices have a significant impact on various aspects of women's life including health, emotional and mental well-being, and lifestyle [7].…”
Section: Introductionmentioning
confidence: 99%